LAYOUT USING SYSTEMATIC LAYOUT PLANNING (SLP) IN PT KASOMALANG CRUSHING PLANT (KCP) SUBANG - Anita Sapitri Agustin; Estu Widarwati; Kuncorosidi Kuncorosidi (STIESA Press, 2019)
PT Kasomalang Crushing Plant (KCP) Subang is one of industries located in Subang regency especially in Kasomalang Kulon engaged in quarrying not metal, which is an activity of andesite rocks from nature, especially lava rocks for reduced size grain. The companies in operation process would want a high productivity with a minimum total cost of production and implementation methods work effectively and efficiently. After observation turns layout arrengement condition PT KCP Subang has yet to match the layout that is effective and efficient. There is a track material in problem, which should be directly processed but with the storage of raw materials while in an area that does not allow that on the outskirts of the main road causing disruption of operations such as congestion in the area. This study was conducted to determine the total material movements from the moment of initial layout, layout alternative I and layout alternative II. The study was conducted through method approach systematic layout planning (SLP). The result showed that the total moment of transfer of material occurring from initial layout reached 13.458.560 m/year, on the layout alternative I reached 13.540.160 m/year and on layout alternative II reached 7.860.800 m/year. From the three layout, the layout that gives total material movement smallest moments are layout alternative II.